2023
DOI: 10.1007/s11356-023-26745-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental economic analysis of speed reduction measure onboard container ships

Abstract: The International Maritime Organization (IMO) has concerned significant care to the reduction of ship emissions and improvement of energy efficiency through operational measures. One of those measures is ship speed reduction, which is classified as a short-term measure; in which the speed is reduced below its designed value. The present paper aims at evaluating the potential energy efficiency, and environmental and economic benefits because of applying speed reduction measures. The research methodology depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, some studies have developed mathematical models to analyze the factors affecting carbon intensity. Elkafas found that carbon intensity values depend on the number of trips per year, the number of passengers carried, and the amount of fuel consumed, and that proper deceleration reduces the ship's emission rate [22]. Sun modeled the speed of a time-chartered vessel with CII penalties included and found that the larger the vessel, the more carbon emissions, and that carbon intensity and CII penalties are reduced when the charter speed is reduced for the same amount of time [23].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, some studies have developed mathematical models to analyze the factors affecting carbon intensity. Elkafas found that carbon intensity values depend on the number of trips per year, the number of passengers carried, and the amount of fuel consumed, and that proper deceleration reduces the ship's emission rate [22]. Sun modeled the speed of a time-chartered vessel with CII penalties included and found that the larger the vessel, the more carbon emissions, and that carbon intensity and CII penalties are reduced when the charter speed is reduced for the same amount of time [23].…”
Section: Related Workmentioning
confidence: 99%
“…Concerning the maritime sector, responsible today for nearly 3% of global CO2 emissions (1 Gton/year), the International Maritime Organization (IMO) published in 2018 a long-term strategy targeting to cut 40% of CO2 emissions per transport work by 2030, pursuing efforts towards 70% by 2050 [1]. To reach this target, many measures can be adopted in different time horizons, including vessel optimization, speed reduction, voyage optimization, and the use of alternative fuels and/or propulsion technologies [2][3][4][5]. In particular, the latest two have been investigated in recent literature by many authors, as they have the potential to cut emissions in the most significant way [6,7], although some of the alternative solutions are not ready on the market yet.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce vessels' emissions and decarbonize the shipping sector [8,9], different measures could be put in place [10,11], acting at different levels of the vessels. The ship emission reduction measures include optimizing the efficiency of the ship engine by using waste heat recovery [12,13], working on alternative propulsion technologies such as wing sails [14] or electric hybrid propulsion [15], reducing ship resistance via trim optimization [16] or an enhanced vessel design [17], and using voyage optimization measures such as onboard energy management [18] or slow steaming concept [19,20].…”
Section: Introductionmentioning
confidence: 99%